Low-Cost In vitro Propagation of Oil Palm Through the Use of Bulk/Commercial Agar and Sugar - Nazhri Simamora, Arfan; Caesar Hidayat, Taufiq; Nazri, Erwin (Jurnal Penelitian Kelapa Sawit, 2024)
The in vitro propagation application in oil palm serves various purposes, such as the multiplication of elite tenera clone varieties, the provision of dura and pisifera parent trees for semi-clonal and bi-clonal varieties, and the conservation of germplasm. However, this method incurs high costs, especially for culture media, including carbon sources (sugar), solidifying agents (agar), and growth regulators. Efforts to reduce costs involve commercial sugar and agar, which are more affordable than their analytical-grade counterparts. This research indicates that commercial agar and sugar use in culture development media results in the best embryo weight increase of 9.76 grams or 4.6 times the initial weight. Significant differences are observed in the individual factors of commercial agar and sugar, with weight increases of 9.00 and 8.56 grams, respectively. There is no difference in necrosis rates between analytical and commercial agar and sugar, with a culture necrosis rate of < 25%. Combining analytical agar and commercial sugar in shoot cultures produces the most significant shoot weight increase, 10.6 grams or five times the initial weight. The most significant increase in shoot height comes from using analytical agar and commercial sugar, with an increase of 6.39 cm. The highest leaf count increase is achieved using analytical agar, with 14.7 leaves (2.6 times the initial count). Using commercial agar and sugar as substitutes for analytical agar and sugar can reduce costs by up to 45.49% for agar and 98.54% for sugar per liter of media. The implementation of commercial agar and sugar has the potential to significantly reduce production costs on a mass or commercial scale in vitro propagation efforts for oil palm plants.